Naphthalene diimide copolymers by direct arylation polycondensation as highly stable supercapacitor electrode materials - Sharma, Sandeep; Soni, Roby; Kurungot, Sreekumar; Asha, S. K. (Macromolecules, 2018)
Conjugated donor-acceptor copolymers based on naphthalene diimide (NDI) as acceptor and thiopheneterminated oligophenylenevinylene as donor moieties (P-1 and P-2, respectively) were synthesized using the direct (hetero) arylation (DHAP) polymerization route. Nitrile groups were introduced at the vinylene linkage in one copolymer (P-2) to fine-tune its electrochemical properties. Both polymers show) pi-pi* transition in the 300-480 nm region and intramolecular charge transfer (ICT) from thiophene to NDI in the 500-800 nm region in the absorption spectra. P-2 exhibits a blue-shifted intramolecular charge transfer (ICT) band in the absorption spectrum as well as a lower reduction potential in the cyclic voltammogram compared to the analogous polymer without the nitrile substitution (P-1). The two polymers were evaluated as type III supercapacitor materials by preparing composite electrodes with carbon nanotubes (CNTs) and employing 0.5 M H2SO4 as the electrolyte. Their performance was compared with that of P(NDI2OD-T2) as a reference polymer. The polymer P-2 based supercapacitor exhibits a specific capacitance of 124 F/g with excellent stability up to 5000 cycles with almost 100% retention of the initial capacitance in the potential window of -0.7 to 0.5 V. Compared to P-2, P-1 exhibits a specific capacitance of 84 F/g, while the corresponding value for the reference polymer P(NDI2OD-T2) is 61 F/g under identical conditions.